2001
DOI: 10.1001/archopht.119.4.516
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Regression of Optic Gliomas

Abstract: To demonstrate spontaneous regression of large, clinically symptomatic optic pathway gliomas in patients with and without neurofibromatosis type 1 (NF-1). Methods: Patient cases were collected through surveys at 2 consecutive annual meetings of the North American Neuro-Ophthalmology Society (NANOS) and through requests on the NANOSNET Internet listserv. Serial documentation of tumor signal and size, using magnetic resonance imaging in 11 patients and computed tomography in 2 patients, was used to evaluate clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(41 citation statements)
references
References 30 publications
1
39
0
1
Order By: Relevance
“…We have identified neurofibromatosis and the presence of a visual pathway glioma as important factors in predicting regression, and other studies have gone further, in suggesting that partial treatment may initiate tumor regression. Parsa et al[ 5] suggested that partial tumor debulking, biopsy, radiotherapy or chemotherapy may play a role in initiating tumor apoptosis. Others have further described needle biopsy or minor debulking as instigators to the regression, citing growth factors and other endogenous reactions as the mechanism [7, 13,19,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have identified neurofibromatosis and the presence of a visual pathway glioma as important factors in predicting regression, and other studies have gone further, in suggesting that partial treatment may initiate tumor regression. Parsa et al[ 5] suggested that partial tumor debulking, biopsy, radiotherapy or chemotherapy may play a role in initiating tumor apoptosis. Others have further described needle biopsy or minor debulking as instigators to the regression, citing growth factors and other endogenous reactions as the mechanism [7, 13,19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Of the factors that have been suggested as positive associations for tumor regression, the association with neurofibromatosis has been the more widely reported. Over 15 reports of the spontaneous regression of low-grade gliomas in association with neurofibromatosis type 1 have been reported [5,6,7,8,9,10,11,12]. The consideration of spontaneous regression is significant, as it would allow a significant number of patients to avoid the side effects of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Case reports have even described spontaneous regression of some tumors (Rozen, Joseph & Lo, 2008;Parsa, Hoyt, Lesser, Weinstein, Strother, Hoyt, 2001). This is in contrast to adult…”
Section: Childhoodmentioning
confidence: 99%
“…Bazı hastalarda tümör kendiliğinden gerileyebilir. 12 Tümör orbitada sınırlıysa, aşırı bir proptozise ve optik atrofiye neden olmuyorsa ve görmeyi tehdit etmiyorsa izlem önerilir. Tedavi yöntemi olarak 5 yaş altı çocuklarda kemoterapi tercih edilebilir.…”
Section: Sonuçlarunclassified